2016
DOI: 10.3389/fmicb.2016.00077
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution of Archaeal Ammonia Oxidizing Ecotypes in the Atlantic Ocean

Abstract: In marine ecosystems, Thaumarchaeota are most likely the major ammonia oxidizers. While ammonia concentrations vary by about two orders of magnitude in the oceanic water column, archaeal ammonia oxidizers (AOA) vary by only one order of magnitude from surface to bathypelagic waters. Thus, the question arises whether the key enzyme responsible for ammonia oxidation, ammonia monooxygenase (amo), exhibits different affinities to ammonia along the oceanic water column and consequently, whether there are different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
71
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 76 publications
11
71
1
Order By: Relevance
“…We did, however, observe a relatively sharp transition at approximately the r t 5 26 kg m 22 isopycnal, just below the euphotic zone and at the maximum NO3 : Si, suggesting that niche differentiation between the WCA and WCB ecotypes may be driven by substrate (ammonium) flux. These data support the observations of Sintes et al (2013Sintes et al ( , 2015Sintes et al ( , 2016 and Smith et al (2015), who suggested that the shallow and deep ecotypes are adapted to "high" and "low" ammonium concentrations, respectively. We posit, however, it is not ammonium concentration, but rather ammonium flux, through these depths that is more likely a driver of niche differentiation, as [NH 1 4 ] in our dataset is below 120 nM at all depths.…”
supporting
confidence: 91%
“…We did, however, observe a relatively sharp transition at approximately the r t 5 26 kg m 22 isopycnal, just below the euphotic zone and at the maximum NO3 : Si, suggesting that niche differentiation between the WCA and WCB ecotypes may be driven by substrate (ammonium) flux. These data support the observations of Sintes et al (2013Sintes et al ( , 2015Sintes et al ( , 2016 and Smith et al (2015), who suggested that the shallow and deep ecotypes are adapted to "high" and "low" ammonium concentrations, respectively. We posit, however, it is not ammonium concentration, but rather ammonium flux, through these depths that is more likely a driver of niche differentiation, as [NH 1 4 ] in our dataset is below 120 nM at all depths.…”
supporting
confidence: 91%
“…albertensis clade had values > 1, indicating that positive selection is ongoing in this branch. This statement is also supported by clearly distinguishable oligotypes between the two lineages at the level of the 16S rRNA gene, implying probable ecotype level differentiation (e.g., Sintes et al, 2016). Some obvious phenotypic features between the two lineages support this view.…”
Section: Discussionmentioning
confidence: 89%
“…>200-500 m), whereas high-ammonia adapted ecotypes dominate more productive sites such as subpolar and equatorial upwelling regions (11,12). Differences in the TEX 86 -ammonia oxidation rate responses of these ecotypes potentially offer an explanation for regional TEX 86 -temperature correlations.…”
Section: Cellular Energy Balance and The Synthesis Of Gdgts: The Redumentioning
confidence: 99%
“…Based on the phylogeny of their ammonia monooxygenase gene, the planktonic Thaumarchaeota are divided into two distinct clusters, the Water Column Cluster A that is most abundant in the epi-and upper mesopelagic (above ∼200 to ∼500 m, depending on location) and the Water Column Cluster B that dominates thaumarchaeal assemblages in the deeper mesopelagic and bathypelagic (7-10). These clusters putatively represent thaumarchaeal ecotypes adapted to high and low ammonium flux, respectively (11,12).Thaumarchaeota produce GDGTs containing from zero to four cyclopentane rings (GDGT-0 to GDGT-4) or four cyclopentane rings and one additional cyclohexane ring (e.g., in crenarchaeol; see SI Appendix, Fig. S1).…”
mentioning
confidence: 99%